Ask Question
14 July, 18:21

Use the equation 8+x + (-5) = (-4) + x+7

+1
Answers (1)
  1. 14 July, 19:46
    0
    Answer:True: 8+x + (-5) = (-4) + x+7

    Step-by-step explanation:

    1st Step

    Remove parenthesis:

    8 + x + - 5 = - 4 + x + 7,

    2nd Step

    Subtract or Cancel X from both sides:

    3rd Step

    Simplify

    8 - 5 = - 4 + 7

    3 = 3
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Use the equation 8+x + (-5) = (-4) + x+7 ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers